Physical activities gamification with smart board - Feitosa, Juliana da Costa; Conrado, Rafael Ragozoni (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2023: Anais do XXV Simpósio de Realidade Virtual e Aumentada, 2023)
Physical activities are important for a healthy and balanced life. There are many physical exercises designed to stimulate different aspects of the body, such as the cardiovascular system or each of the muscle tissues. However, there is a certain resistance to their routine performance due to their monotonous and repetitive nature. In order to overcome this barrier present in various tasks, one can resort to gamification, which uses typical elements of games, especially digital ones, to make any activities more interesting. Concepts of gamification have been used in the context of physical exercise to try to stimulate the performance of physical activity among adults, and to contribute to the maintenance of an active life among users. This was done through a gamified software made on the Unity platform to be used on the Huawei IdeaHub smartboard that runs on Windows operating system and has a camera. The software has a menu with statistics, achievements and exercises with description of the activity. The user performs exercises provided by the software, viewing information about the activity and with the camera of the IdeaHub, capturing the movements to count the exercises.